Public law librarianship objectives, challenges, and solutions - Selwyn, Laurie, 1956-; Eldridge, Virginia, 1954-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book aims to introduce firsthand knowledge on the funding, organizational structures, and governance related to public law libraries, including comprehensive research for current and future public law librarians to provide administrative guidance and professional sources essential for running a public law library"--Provided by publisher.
Introduction to public law libraries -- Patron base -- Governance and organizational structures -- General library management -- Personnel -- Public relations -- Collection development -- Technology, contracts, and electronic resources -- Technical services -- Public services.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed August 23, 2012).
Keywords: Law libraries -- United States; Law libraries -- United States -- Administration; Law libraries -- United States -- History; Collection development; Federal and national law libraries; Organizational structures; Patron base; Private law librarians; Public law librarians; Reference service; Electronic books